Experiences of caregivers implementing HIV and AIDS services within community-based organizations (CBOS) in rural Maseru: Lesotho - Makoae, Mamello Genevieve (University of the Free State, 2015)
Prevalence of HIV in Lesotho has remained at the plateau of 23% for years, and this has increased the demands in care and support of the infected people (Akinkugbe and Mohanoe, 2009:132). With increased demand in care, the communities are forced to take charge and to voluntarily provide care and support to their relatives, friends and neighbours hence the establishment of the support groups and the Community Based Organizations (CBOs) which implemented HIV and AIDS activities in the communities at the grassroots (Kell and Walley, 2009:7-8). A qualitative research was employed using focus group interviews to explore and describe the experiences of HIV and AIDS Caregivers within these CBOs. Tesch’s (1990) method of data analysis as adopted and explained by Creswell (2009:185) was used to analyze data. A purposive sample of HIV and AIDS caregivers was used and their experiences were categorized into activities, challenges, motivating factors and recommendations. The recommendations emanated from the discussions included the need to: design a standard guideline for community-based caregivers; include the caregivers in the budget for incentives, design the training guide for refresher courses and provide routine supervision and mentoring. The discussions also point to need for the local NGOs to involve the communities in their planning.
Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2015
Keywords: HIV infections -- Lesotho -- Maseru; Caregivers -- Psychology; Community health services -- Lesotho -- Nursing; AIDS (Diseases) -- Lesotho -- Maseru